Agents, endowments, and path-dependence: a model of multi-jurisdictional regional development - Clark, G; Tracey, P; Smith, H (Franz Steiner Verlag, 2001)
In this paper, we emphasize the links between agent-centred decision-making and the role and status of the context in which decision-making takes place. Our problem is simple yet complex: how can we explain the acknowledged importance of path-dependence while allowing for agents to step away (even defect) from local imperatives in the light of European integration and globalisation? To answer this question requires adding-on three conceptual building blocs to our previously introduced framework. Beginning with a critique of W. B. Arthur’s notion of path dependency and drawing upon the work of Herbert Simon, we introduce a contingent model of rationality and decision-making. We then suggest how and why social customs and norms–relational capital–may be important place-specific endowments at worst constraining, perhaps neutralising, sometimes enabling, and at best promoting agents’ decision-making. Given a multi-jurisdictional environment, the third piece of the analysis concentrates on the process whereby agents may take advantage of the possibilities offered by other jurisdictions (a common-scale process of competition and differentiation) and other levels of governance and regulation (an up-scale or down-scale process of competition and differentiation). Implications are drawn for the role and status of place-specific relational capital in the context of accelerating European integration. While recognising the empirical reality of path-dependence, we dispute the necessity of its persistence.